HUBUNGAN ANTARA MANAJEMEN PENGETAHUAN DAN KEBERLANJUTAN ORGANISASI: PERAN SERTIFIKASI ISO 9001 - Bimmo Dwi Baskoro; Heri Sapari Kahpi; Iwan Ridwan (Jurnal Ilmiah Ekonomi Bisnis, 2022)
The purpose of this study is to determine the influence of the determinants of knowledge management on organizational sustainability. The study also investigated performance differences among ISO 9001 certified and non-certified companies. A total of 156 employees from various private companies in Bekasi were used as samples. The SEM-PLS approach is used to test hypothetical models. Independent sample t-test testing is used to see the difference between ISO 9001 certified and non-certified companies. Based on the results of research it is known that the storage of knowledge plays a key role in the generation of knowledge, sharing, and utilization. Knowledge management has a significant impact on organizational sustainability.